The reptile room - Snicket, Lemony; Helquist, Brett (London : Egmont Books, 2001)
After narrowly escaping the menacing clutches of the dastardly Count Olaf, the three Baudelaire orphans are taken in by a kindly herpetologist with whom they live happily for an all-too-brief time.
Includes audiobook.
Keywords: Humorous fiction; Orphans -- Fiction